An Intuitionistic Fuzzy Soft Software Life Cycle Model - Kalayathankal, SJ; Abraham, JT; Kureethara, JV (International Journal of Computer Sciences and Engineering, 2025)
Software engineering is a collaborative effort. It involves processes, people and technology. As a massive action, it needs sound evaluation techniques to ensure its efficacy and appropriateness. No software engineering firm look anything lower than the most efficient model. A proper build up will then decide the prospects including the successful completion of the project. This study intends to develop similarity measures between intuitionistic fuzzy soft sets (IFSSs). The proposed model is applied to five software life cycle models (SLCMs) so as to select the most appropriate one.